1983
DOI: 10.1093/carcin/4.11.1483
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of chloroethylene oxide being the reactive metabolite of vinyl chloride towards DNA: comparative studies with 2,2′ -dichloro-diethylether

Abstract: The roles of chloroethylene oxide (CEO) and chloroacetaldehyde (CAA) in carcinogenicity of vinyl chloride (VC) have been studied by comparing biological effects of VC exposure with those of 2,2'-dichlorodiethylether (bis(chloroethyl)ether, BCEE) as a metabolic precursor of CAA. Biological end-points investigated were covalent protein binding, nucleic acid (RNA and DNA) alkylation and the potency of the two chemicals to induce preneoplastic ATPase-deficient foci in rat liver. After exposure of rats to [1-14C]BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…l-Chlorooxirane was shown to react with calf thymus DNA to form both lA/6ethenoadenosine and AP.S-ethenoguanine considerably more effectively than did 2-chloroacetaldehyde in experiments where the reaction was quenched after 10 half-lives of the epoxide (5) (Figure 2). The lack of formation of N1 -(2-oxoethyl)guanine from 2-chloroacetaldehyde is consistent with the reported absence of its in vivo formation with chemicals that generate this electrophile through metabolism (4,30).…”
supporting
confidence: 85%
“…l-Chlorooxirane was shown to react with calf thymus DNA to form both lA/6ethenoadenosine and AP.S-ethenoguanine considerably more effectively than did 2-chloroacetaldehyde in experiments where the reaction was quenched after 10 half-lives of the epoxide (5) (Figure 2). The lack of formation of N1 -(2-oxoethyl)guanine from 2-chloroacetaldehyde is consistent with the reported absence of its in vivo formation with chemicals that generate this electrophile through metabolism (4,30).…”
supporting
confidence: 85%
“…The latter yields chloroacetaldehyde as intermediate metabolite, but not chloroethylene oxide. By this way it was concluded (Gwinner et al, 1983) that the biologically relevant alkylating agent was in fact the epoxide metabolite, chloroethylene oxide. This was later confirmed by independent ways (Guengerich, 1992).…”
Section: A Metabolism and Toxicokineticsmentioning
confidence: 99%
“…7 , Table 1 ) [ 27 ]. Gwinner et al [ 36 ] reported that 2,2′-dichlorodiethyl ether, which is hydroxylated and decomposes to 2-chloroacetaldehyde, did not yield etheno DNA adducts or N 7 -(2-oxoethyl) dGuo when given to rats nor did it produce the preneoplastic foci, a hallmark of vinyl chloride carcinogenesis. The results were congruent with in vitro results on the labeling of DNA by 14 C-vinyl halides in microsomal reactions, with the epoxides and 2-haloacetaldehydes being quenched by the addition of enzymes (epoxide hydrolase and alcohol dehydrogenase) (Fig.…”
Section: Modification Of Dna By Products Of Vinyl Chloride and Other Olefins Generates Etheno Adductsmentioning
confidence: 99%
“…7 ). The results have biological relevance in that other chemicals that can generate 2-haloacetaldehydes after metabolism are not very carcinogenic [ 36 ] (Fig. 7 ).…”
Section: Chemical Mechanisms Of Formation Of Etheno Adductsmentioning
confidence: 99%